Characterizing Learning-motivating Teachers among Hospitality Management Students of a Higher Education Institution in the Philippines - C. Bañagale, Ana; D. Dagdag, Januard; C. Galiza, Clarinda (International Journal of Psychosocial Rehabilitation, 2020)
This descriptive study aimed to explore the attributes of teachers that can aid students’ motivation to learn by considering the perception and verbal responses of 143 Bachelor of Hotel and Restaurant Management students. Data were gathered through a scale and personal interviews whose data were analyzed using descriptive statistics and content analysis, respectively. Findings showed that the students’ motivation to learn associates with teachers’ personality traits during instruction, teaching skills reflected by their mastery of the subject matter and strategies in teaching, ways of setting the learning goals, instructional materials used, and ways of giving reinforcement. Among these five factors, teachers’ personality traits and teaching skills were claimed to contribute most to their learning motivations. Such confirms that having a good sense of humor, good relationships with students, being open to suggestions and opinions, giving respect to students, imposing but abiding by classroom rules, and showing teaching effectiveness in terms of both content and pedagogies are among the most learning-motivating characteristics of teachers. Hence, various implications and strategies like enrolling in graduate school or professional education subjects and attending seminars on pedagogy were offered to the department to meet the needs and expectations of the students.